Bond Kit/ Vignesvaran Suppiah, Malini Deepa Kaliappan And Shella Govindarajan - Suppiah, Vignesvaran; Kaliappan, Malini Deepa; Govindarajan, Shella (2023)
BOND KIT is an innovation implemented to help students visualize the formation of chemical bonds, especially ionic and covalent bonds. The kit enables students to understand and visualize the transfer and sharing of electrons and identify metal and non-metal atoms, which helps in understanding the concept of bonding. The bond kit consists of electron rings with tiny holes, which are made from easily available materials such as mounting boards and beads. The Bond Kit also comes with a card game, which consists of questions ranging from easy to high-order thinking to be solved by students in groups. Twenty students were selected as respondents to evaluate the effectiveness of the Bond Kit. Two instruments were used to obtain data for the study. A pre-post question set and a 5-point Likert scale questionnaire were administered as a survey. The data obtained were analyzed using SPSS version 26. There is a significant increase in test scores after the use of Bond Kit. The survey shows students were highly motivated to use the Bond Kit to enhance their understanding. Bond Kit also received high appreciation from experienced chemistry teachers. The copyright of Bond Kit is registered with MyIPO (LY 2023P04611). The Bond Kit is further improvised by adding a special teacher demo kit ordered from the factory.